The Physiological Responses of Preterm Infants to Clustered Care with Three and Five Procedures: A Randomized Crossover Clinical Trial - L Valizadeh; M Avazeh; N Babaei; MB Hosseini; M Asghari Jafarabadi (Iran University of Medical Sciences, 2015)
Abstract Background & Aims: The life of preterm infants admitted to a Neonatal Intensive Care Unit (NICU) is stressful from the moment of birth. In order to reduce the stress imposed on these infants clustered care is recommended. The aim of present study was to compare the physiological responses of preterm infants to clustered care with three and five noninvasive procedures. Material & Methods: This study was a randomized crossover clinical trial. Thirty one preterm infants were studied at 32 weeks age by clustered care with three and five procedures. Primary outcomes such as heart rate, respiratory rate and blood oxygen saturation were assessed. Data analysis conducted with a mixed model method at 0.05 significant level. Results: The findings showed that the mean of oxygen saturation on before, during and after clustered care with three procedures were respectively 97.52, 97.32, 97.84 and in clustered care with five procedures were 97.68, 97.94, 97.65. Heart rate of three procedures were 146.26, 149.90, 149.97 and five procedures were 150.61, 154.77, 154.65. Respiratory rate of three procedures were respectively 51.68, 48.87, 47.71 and five procedures were 49.10, 48.61, 49.48. All of these physiological responses were at normal range. Significant differences were not found between physiological responses of two groups (P>0.05). Conclusion: Clustered care with three procedures is as same as clustered care with five procedures and both of them could be recommended for stable premature infants in 32 weeks.